Can Axis C be a navigation route – CT comparison study between actual and virtual C1 transpedicular screw insertion. (May 2023) - He, Hongwei
Highlights: There is no cortical perforation in C1 transverse foramen, vertebral canal, and medial border of lateral mass along virtual screw based on Axis C in the axial plane. The design method of Axis C can be an inspiration for artificial intelligence screw trajectory design. Axis C is an ideal C1 transpedicular screw trajectory which can be used as a navigation route for computer assisted surgery system. Abstract: Background: Previous studies mainly reported perpendicular and medial inclination insertion methods for C1 transpedicular screw insertion (TSI). Our recent study showed the ideal C1 transpedicular screw trajectory (TST) can be achieved by medial inclination, perpendicular or even lateral inclination insertion, and Axis C can be a reliable trajectory. The purpose of this study is to confirm Axis C is an ideal C1 TST by comparing the cortical perforation differences between actual C1 TSI and virtual C1 transpedicular screw insertion along Axis C (Virtual C1 Axis C TSI). Methods: Firstly, the cortical perforations of the transverse foramen and vertebral canal caused by C1 TSIs in twelve randomly selected patients were evaluated based on their postoperative CT data. Secondly, Virtual C1 Axis C TSIs were performed based on same patients' preoperative CT data. Thirdly, the cortical perforation differences between actual and virtual screws were compared. Results: In actual C1 TSI group, there were thirteen locations of cortical perforation in the axial plane, with five sides in transverse foramen and eight sides in vertebral canal, the cortical perforation rate was 54.2%; the degree of perforation was mild in twelve locations and medium in one location. In contrast, there was no cortical perforation in Virtual C1 Axis C TSI group. Conclusions: Axis C is an ideal trajectory for C1 TSI, it can be utilized as a navigation route for computer assisted surgery system.